Structural Features of the Intellectual Potential of the Regions and its Impact on the Development of the Country - D. M. Kangalakova; D. A. Rakhmetova (Экономика: стратегия и практика)
In Kazakhstan, the approach to this area is not sufficiently developed, there is no systematic and scientific justification in the management of intellectual resources of the country and regions. Therefore, Kazakhstan is faced with the urgent issue of creating opportunities for the effective use of intellectual capital in the regions, working out management mechanisms and technologies. The development of the region can be traced to the development of intellectual potential in the region. Given the high intellectual potential of the population living in the region, it can be concluded that this region is not lagging in economic development. To determine the potential of the local population, it is necessary to consider the factors influencing it. In this connection, the purpose of this article is to determine the level of factors affecting intellectual potential in the regions of Kazakhstan. During the study, the methods of observation and comparison, system analysis, synthesis and logic were used. In the course of the analysis, it was revealed that in Almaty, Nur-Sultan, Karaganda region, East Kazakhstan region, the components constituting the intellectual potential show a high dynamics of development. There are also regions with low rates of development of components of intellectual potential, these are Almaty region, Akmola region, Turkestan region. For the complex and varied development of regions, appropriate strategic and tactical management decisions should be made, considering the specifics of each region. The factors identified because of the study can become the basis for developing a methodology for assessing the intellectual potential of regions. The research results can be used in programs and strategic plans aimed at developing the intellectual potential of the regions.